A fragile freedom : African American women and emancipation in the antebellum city - Dunbar, Erica Armstrong (Society and the sexes in the modern world., 2008)
Chronicling the lives of African American women in the urban north of America (particularly Philadelphia) during the early years of the republic, 'A Fragile Freedom' investigates how they journeyed from enslavement to the precarious state of 'free persons' in the decades before the Civil War.